Assessment of the effect of frequency of low-level laser therapy exposure at different intervals on orthodontic tooth movement - A systematic review and meta-analysis - Poornima R Jnaneshwar; Keerthi Venkatesan; Tsander Prince; Vijayalakshmi Pethuraj; Krishnaraj Rajaram; Sachin Bhat (Wolters Kluwer Medknow Publications, 2023)
OBJECTIVE: To assess the optimal intervals of exposure of low-level LASER therapy (LLLT) that would optimally accelerate orthodontic tooth movement. Second objective was to quantitatively analyze the difference in the time taken for alignment of anterior teeth with and without the application of LASER. MATERIALS AND METHODS: PROSPERO database registry was done (CRD42020196472) and review was conducted based on PRISMA guidelines. A search was systematically conducted in five major electronic databases without restrictions up to June 2020 along with a hand search of selected journals. The quality of evidence was assessed using the Grading of Recommended Assessment, Development, and Evaluation tool, risk of bias using Cochrane risk of bias tool, and meta-analysis was carried out using RevMan 5.4 software. RESULTS: Ten randomized controlled trials which met the inclusion criteria were evaluated and tabulated. A random-effects meta-analysis demonstrated that there is a statistically significant increase in the orthodontic tooth movement when patients were exposed to minimum of four intervals of LLLT in the first month, at P =0.03 by a standard mean difference of 0.46 mm with an overall heterogeneity of I2 = 0% at 95% confidence interval. There was a statistically highly significant reduction in the number of days taken for alignment of anterior teeth with the application of LASER (P < .00001). CONCLUSION: Application of LLLT for minimum of four irradiations in the first month has yielded better results in accelerating orthodontic tooth movement than application of LLLT once a month.